Archaic and classical Greek Sicily : a social and economic history - De Angelis, Franco (Greeks overseas, 2016)
Ancient Greek migrants in Sicily produced societies and economies that both paralleled and differed from their homeland. Explanations for these similarities and differences have been hotly debated. On the one hand, some scholars have viewed the ancient Greeks as one in a long line of migrants who were shaped by Sicily and its inhabitants. On the other hand, other scholars have argued that the Greeks acted as the main source of innovation and achievement in the culture of ancient Sicily, a culture that was still removed from that of mainland Greece. Neither of these positions is completely satisfactory. This book reveals and explains the similarities and differences between developments in Greek Sicily and the mainland, and brings greater clarity to the parts played by locals and immigrants in ancient Sicily's impressive achievements